Inverse association between altitude and obesity: A prevalence study among andean and low‐altitude adult individuals of Peru. Issue 4 (3rd March 2016) - Woolcott, Orison O.; Gutierrez, Cesar; Castillo, Oscar A.; Elashoff, Robert M.; Stefanovski, Darko; Bergman, Richard N.
Abstract : Objective: To determine the association between altitude and obesity in a nationally representative sample of the Peruvian adult population. Methods: This is a cross‐sectional analysis of publicly available data from the Food and Nutrition National Center (CENAN, Peru), period 2009‐2010. The Prevalence ratio of obesity and abdominal obesity was determined as a measure of association. Obesity and abdominal obesity were diagnosed based on direct anthropometric measurements. Results: The final data set consisted of 31, 549 individuals ≥20 years old. The prevalence ratio of obesity was as follows: 1.00 between 0 and 499 m (reference category), 1.00 (95% confidence interval 0.87‐1.16) between 500‐1, 499 m, 0.74 (0.63‐0.86) between 1, 500‐2, 999 m, and 0.54 (0.45‐0.64) at ≥3, 000 m, adjusting for age, sex, self‐reported physical activity, out‐migration rate, urbanization, poverty, education, and geographical latitude and longitude. In the same order, the adjusted prevalence ratio of abdominal obesity was 1.00, 1.01 (0.94‐1.07), 0.93 (0.87‐0.99), and 0.89 (0.82‐0.95), respectively. We found an interaction between altitude and sex and between altitude and age ( P  < 0.001, for both interactions) on the association with obesity and abdominal obesity. Conclusions: Among Peruvian adult individuals, we found an inverse association between altitude and obesity, adjusting for multiple covariates. This adjusted association varied by sex and age.